Towards intelligent thermal energy management of eco-industrial park through ontology-based approach - Zhang, Chuan (2018)
An ontology-based approach for thermal energy management of eco-industrial park is proposed in this paper. The ontology captures core concepts of this domain as well as the relationships between them; together with instances, the ontology can serve as knowledge base for related energy management tools. The development of this application ontology is based on existing knowledge base, e.g. OntoCAPE in this paper. The advantages of ontology-based approach are shown by an application case, the case shows how ontology can overcome data heterogeneity both structurally and semantically through its own reasoning ability, then allow intelligent decision making by using disparate data from remote databases, which implies the possibility of self-optimization without human intervention in the future scenario. With properly designed cyber-infrastructure systems, the prospective application of the ontology-based approach can unleash the potential of artificial intelligence for eco-industrial park thermal energy management in the future.